1998
DOI: 10.1080/00207284.1998.11491545
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Patients: Their Construction in Group Therapy

Abstract: Written from the perspective of intersubjective theory, this article addresses how the leader and group members co-construct the difficult patient. Too often, therapists and patients have tended to attribute difficulties in therapy groups to "the difficult patient" without appreciating how they themselves contribute to the construction, the needs this construction serves, and the potential value of such patients to the group. Mistakes in group leadership, vicissitudes of intersubjectivity, disturbing intrapsyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Following the introduction of the notion of narcissism into the field of organizational behavior, some studies have found that many leader behaviors are actually influenced by the narcissistic personality traits of the leaders ( de Vries and Miller, 1985 ). Ouimet (2010) pointed out that narcissistic leaders exhibit charisma, excessive pursuit of self-influence, false motives and, in the process, suppress employee performance.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Following the introduction of the notion of narcissism into the field of organizational behavior, some studies have found that many leader behaviors are actually influenced by the narcissistic personality traits of the leaders ( de Vries and Miller, 1985 ). Ouimet (2010) pointed out that narcissistic leaders exhibit charisma, excessive pursuit of self-influence, false motives and, in the process, suppress employee performance.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In their seminal text, Yalom and Leszcz (2005) dedicate an entire chapter to identify common problematic group members and provide clinical recommendations for working with these members. Importantly, group researchers have also sought to identify factors that lead to problematic group member behavior (Brown, 2006;Gans & Alonso, 1998), as well as examined problematic group processes, such as negative working relationships (Krogel et al, 2013) and negative group climate (Johnson, Burlingame, Ol-This article was published Online First December 2, 2019.…”
mentioning
confidence: 99%
“…sen, Davies, & Gleave, 2005;Mackenzie, 1981). Group researchers note the role of the other group members, group dynamics, and the group leader as important sources that contribute to problematic member behaviors in addition to intrapsychic factors (Brown, 2006;Gans & Alonso, 1998;Yalom & Leszcz, 2005).…”
mentioning
confidence: 99%
“…Exposing such feelings in a group setting was likely intolerable, and he instead sought safety by attempting to wrest control of the group. The "difficult patient" in group therapy usually has accomplices: group dynamics influenced by therapists and other group members often coalesce with the individual's problematic behavior to coconstruct the difficulty (Gans & Alonso, 1998). In this case, group members may have been unconsciously relying on Ron to do the "storming" (Tuckman & Jensen, 1977) work on their behalf, expressing their collective anxieties with an aggression that may have felt somewhat empowering.…”
Section: Morrismentioning
confidence: 99%